Evolution of a light-harvesting protein by addition of new subunits and rearrangement of conserved elements: Crystal structure of a cryptophyte phycoerythrin at 1.63-Å resolution - Wilk, Krystyna E. (The National Academy of Sciences, 1999)
Cryptophytes are unicellular photosynthetic algae that use a lumenally located light-harvesting system, which is distinct from the phycobilisome structure found in cyanobacteria and red algae. One of the key components of this system is water-soluble phycoerythrin (PE) 545 whose expression is enhanced by low light levels. The crystal structure of the heterodimeric α(1)α(2)ββ PE 545 from the marine cryptophyte Rhodomonas CS24 has been determined at 1.63-Å resolution. Although the β-chain structure is similar to the α and β chains of other known phycobiliproteins, the overall structure of PE 545 is novel with the α chains forming a simple extended fold with an antiparallel β-ribbon followed by an α-helix. The two doubly linked β50/β61 chromophores (one on each β subunit) are in van der Waals contact, suggesting that exciton-coupling mechanisms may alter their spectral properties. Each α subunit carries a covalently linked 15,16-dihydrobiliverdin chromophore that is likely to be the final energy acceptor. The architecture of the heterodimer suggests that PE 545 may dock to an acceptor protein via a deep cleft and that energy may be transferred via this intermediary protein to the reaction center.